Life on the Edge: Extreme Homes - Brian Sargent (NewYork Cambridge University Press, 2014)
Would you live in space? How about in a cave? Would you mind living below a volcano? Explore the many dangerous and unusual places people can live all over (and outside of!) the world.
B1